Similarities and differences between intermittent hemodialysis and sustained low-efficiency dialysis - Sasidaran Kandasamy; K. G. Sunil Reddy; Nivesh Subburaj (Wolters Kluwer Medknow Publications, 2024)
Acute kidney injury (AKI) is a multifaceted syndrome with diverse etiologies encountered very frequently in all critical care service units. Time and again, multiple researchers have proven its independent contribution to increasing morbidity and mortality in hospitalized children and adults. This undeniable fact has guided the development of newer strategies and logical concepts that have led to new modalities of treating AKI. In the absence of curative medical therapy, kidney replacement therapy (KRT) is considered the primary supportive therapy for AKI, and when initiated at the right time, it has the potential to bridge the gap toward cure. Among all KRT methods, blood-based dialysis occupies a prominent role and has now become the cornerstone of treatment for critically ill children with AKI. Two major methods usually employed are "intermittent hemolysis" (IHD) and "continuous kidney replacement therapy" (CKRT). Currently, a third method called "sustained low-efficiency dialysis (SLED)" is gaining momentum in critical care. It is a hybrid method; in simpler terms, it is a slow and prolonged IHD that may carry a few of the critical merits of CKRT. This narrative review article sheds light on SLED, as well as its comparison to IHD in critical care practice.